(untitled) (Ustozlar uchun, 2025)
This article explores two related topics: the structure of a podcast outline and the global role of English. Podcasts are an increasingly popular medium for sharing information, learning, and entertainment. A clear and organized outline ensures that the podcast is engaging and easy to follow. English, as a global language, connects people from different countries and cultures. Its widespread use in education, business, technology, and media highlights its importance in the modern world. The article discusses the benefits of creating podcast outlines and the influence of English as a universal language